Post a New Question

Algebra

posted by on .

Multiplying sq rts
sqrt18a^7b times sqrt27a^8b^6

Jake 1214-
18 = 9 * 2 then sqrt 18 = 3sqrt2
sqrt a^7 = a^3 * sqrt a

27 = 9 * 3 then sqrt 27 = 3 sqrt3
sqrt a^8 = a^4
sqrt b^6 = b^3
Now just multiply the like-terms together.

3sqrt6 and sqrt2a^4?

  • Algebra - ,

    .. 3sqrt6 and sqrt2a^4?

    So you simplified the problem first as I said above and you get:

    3(a^3)sqrt(2a) * 3(a^4)(b^3)sqrt(3)

    and then you multiply those 2 things together and you get:

    9(a^7)(b^3)sqrt(6a)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question